Co-Inheritance of Sickle Cell Trait and Thalassemia Mutations in South Central Iran - N Saleh-gohari; M Mohammadi-Anaie (Tehran University of Medical Sciences, 2012)
Background: We aimed to determine the incidence of co-inheritance as well as interaction of sickle cell trait (SCT) and αthal/βthal mutations in south and south central of Iran. Method: We employed a PCR and restriction fragment length polymorphism techniques to confirm diagnosis of sickle cell trait. All subjects were screened for any α/β -thalassemia mutations using a gap-polymerase chain reaction and amplification refractory mutations system. Results: Our results showed combination of sickle cell trait and β-globin mutation results in a severe clinical course of similar to sickle cell disease, while coinheritance of α-globin gene defects usually modulates the clinical course. A coexistence of sickle cell trait and α-globin gene mutation was the frequent genotype in overall samples (57. 5%). Conclusion: Sickle cell trait mainly co-inherits with α-globin gene mutation in the south and south central region of Iran. This combination modulates hematological indices and interferes with the SCT diagnosis.